2007
DOI: 10.1038/msb4100116
|View full text |Cite
|
Sign up to set email alerts
|

Chemical combination effects predict connectivity in biological systems

Abstract: Chemical synergies can be novel probes of biological systems.Simulated response shapes depend on target connectivity in a pathway.Experiments with yeast and cancer cells confirm simulated effects.Profiles across many combinations yield target location information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
287
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(303 citation statements)
references
References 58 publications
12
287
0
4
Order By: Relevance
“…The results are complementary to detailed mechanistic models because they impose an upper limit on how much mechanistic information is required to predict bacterial growth. Mechanistic and empirical approaches remain essential to characterize the effects of specific drug pairs (18)(19)(20)(21)(22)(23). Remarkably, however, our results reveal that additional information is often not required to predict the effects of larger combinations of drugs.…”
Section: Discussionmentioning
confidence: 86%
“…The results are complementary to detailed mechanistic models because they impose an upper limit on how much mechanistic information is required to predict bacterial growth. Mechanistic and empirical approaches remain essential to characterize the effects of specific drug pairs (18)(19)(20)(21)(22)(23). Remarkably, however, our results reveal that additional information is often not required to predict the effects of larger combinations of drugs.…”
Section: Discussionmentioning
confidence: 86%
“…In these models, the system is treated as a black box, and it does not require a complete characterization of the biological networks 37,38 . (iii) Model-based combinations in which biological measurements are used to build explicit models of a target network using simulations 39,40 . This approach seems to be one of the most successful in multidrug design.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…Non-linear dynamics including bistability and oscillation are involved in the CREB model. There are eight parameters in the model (16)- (17) and in total 28 possible distinct two-parameter combinations. For the bistable case, when the [CREB1]/[CREB2] ratio in the absence of parameter changes is chosen as the control, the percentage increase of the ratio over the control to perturbations of the 28 parameter pairs has been investigated and it has been shown that the parameter pair (v x , k dy ) exhibits a strong degree of synergism [28].…”
Section: Synergism In the Creb Modelmentioning
confidence: 99%
“…It also depends on the quantities of each perturbation in synergistic combinations. The determination of synergism is crucial to understand combinatorial control in molecular networks, e.g., how cells respond optimally to two or more mixed signals [12][13][14], how to optimize the combinatorial therapies in pharmaceutical development [15][16][17], and how to control the processes of fate decisions [18]. Prior works on synergism have mainly focused on combination drug therapies.…”
Section: Introductionmentioning
confidence: 99%